Avaliação do efeito de palmilhas adaptadas em chinelos no tratamento da fasciopatia plantar: um estudo com moradores do semiárido potiguar - Costa, Ana Rafaella Araújo (2019)
Introduction: Plantar fasciitis (PF) is a subcalcaneal painful syndrome, which was firstly described in 1812. It is the most common cause of pain in the plantar heel region. Estimates highlight that one out of every 10 people will have pain in the lower calcaneal region at some point in life. Most patients report poor quality of life, since pain prevents the accomplishment of activities of daily living (ADL) and the performance of physical activities. Conservative treatments account for 90% of hindfoot pain resolutions and are associated with therapies including joint mobilization, stretching, insoles, shock wave therapy and laser therapy. Nevertheless, the use of insoles is restricted to the application in closed footwear such as shoes and sneakers, and this can be an obstacle to the treatment in cities with hot weather. Objective: To assess the effectiveness of insoles adapted for slippers in pain and function in individuals with PF. Method: Randomized, double-blind, controlled and clinical study involving 66 pa-tients diagnosed with PF, who were randomized into two groups: insole slipper (IS) group (n=34), which received a custom-made slipper (flip-flop) with foot devices and smooth beige synthetic leather cover. The flat slipper group (FS) (n=34) received a slipper (flip-flop) cov-ered with smooth beige synthetic leather, identical to the one used by the intervention group, but without the foot devices. Patients were instructed to wear the slipper at least 4 hours a day for 12 weeks. We held two assessments: one before the intervention protocol (T0) and the second after the 12 weeks of intervention (T12). As the primary outcome, we considered the pain measured through the Visual Analogue Scale (VAS). The secondary outcomes were: foot function by FFI questionnaire Foot Function Index; foot and ankle functionality by FAAM questionnaire Foot and Ankle Ability Measure (FAAM); functional capacity by 6-minute walking test (6MWT); patient’s expectation and satisfaction with treatment by Likert scale; the blinding questionnaire to ascertain patients’ blinding, besides a daily diary to note the hours they wore the slipper every day. Results: The IS group significantly improved morning pain through the morning VAS variable (p=0,016); without differences between groups for end-of-day VAS (p = 0,31), 6MWT (p = 0,45) and FAAM (p = 0,062). Another statistically significant value obtained was from FFI variable, where the IS group unveiled results (p=0,023), thereby showing improvements in foot func-tion after wearing the slipper. Conclusion: Insoles adapted for flip-flops as a 12-week treat-ment for PF-related pain were effective in improving morning pain and foot function.